Mannan-oligosaccharide modulates gut microbiota and enhances immune-metabolic functions in Chinese mitten crab (Eriocheir sinensis): Insights from an in vitro fermentation model - Wei Li; Shubin Liu; Kaiqi Huang; Xiaoling Zhang; Xiaodan Wang; Jian G. Qin; Liqiao Chen; Erchao Li (Aquaculture Reports)
Prebiotics are promising alternatives to antibiotics for enhancing disease resistance in aquaculture, yet their immunomodulatory mechanisms remain poorly understood.This study investigated the regulatory effects of prebiotics through in vitro experiments by directly comparing the effects of seven prebiotics, fructo-oligosaccharides (FOSs), galacto-oligosaccharides (GOSs), Mannan-oligosaccharides (MOSs), inulin, β-glucan, isomaltodextrin (IMO), and xylo-oligosaccharides (XOSs), on the gut microbiota and metabolites in the Chinese Mitten Crab (Eriocheir sinensis). The pH values and digestive enzyme activities of the fermentation broth were measured. Five prebiotics (GOS, MOS, β-glucan, IMO, and XOS) exhibited significant effects, and they were subsequently selected for further analysis of short-chain fatty acid (SCFA) production and gut microbiota composition. After 12 h of in vitro fermentation, the MOS-supplemented group presented minimum pH and maximum trypsin and lipase activities. MOS outperformed other prebiotics, particularly butyric acid, in stimulating SCFA production. Compared with the other treatments, MOS significantly increased the growth of Clostridium and Lactococcus. Notably, MOS-driven butyrate accumulation was linked to the upregulation of anti-inflammatory pathways (e.g., NF-κB inhibition) and enhanced intestinal barrier integrity. Furthermore, MOS suppressed branched-chain fatty acids (BCFAs), potential markers of proteolytic dysbiosis, suggesting its role in mitigating gut inflammation. These findings highlight MOS as a potent immunomodulatory prebiotic for E. sinensis, providing a mechanistic basis for its application in antibiotic-free aquaculture strategies.